Efektivitas E-Wom, Store Atmosphere, Dan Price Dalam Mempengaruhi Purchase Intention - Ikraam, Mochammad Nibraas Faalih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Purchase intention is an important issue to study in various industrial fields at this time, especially the tourism industry, especially restaurant industry. Purposes of this research is to determine the influence of electronic word of mouth (e-WOM), store atmosphere and price on purchase intention at Concrete Cafe. This type of research is quantitative with a population of all potential Concrete Cafe consumers, because the population size is unknown and its nature is dynamic, the sample size was determined using the Lameshow formula and 100 respondents were obtained. The data is primary data collected using a questionnaire. The data was then analyzed using multiple linear regression with the help of SPSS 25. The research results showed that E-Wom on Instagram and Tik-Tok social media did not have a significant effect on Concrete consumers' Purchase Intention. Store Atmosphere and Price have a positive and significant effect on Purchase Intention of Stone Concrete consumers. There is a simultaneous influence (together) of E-Wom, Store Atmosphere, and Price on the Purchase Intention of Concrete Cafe Batu consumers. Abstrak Purchase intention menjadi isu yang penting untuk dikaji di berbagai bidang industri pada saat ini, khususnya industri pariwisata yaitu industri restoran. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh electronic word of mouth (e-wom), store atmosphere dan harga berpengaruh terhadap purchase intention pada Concrete Cafe. Jenis penelitian ini Kuantitatif dengan populasi seluruh calon konsumen Concrete Cafe, karena jumlah populasi tidak diketahui dan sifatnya dinamis maka penentuan jumlah sampel ditentukan dengan rumus Lameshow dan didapat 100 responden. Data merupakan data primer yang dikumpulkan dengan kuisioner. Data kemudian dianalisa dengan regresi linier berganda dengan bantuan SPSS 25. Hasil penelitian menunjukkan E-Wom di Media Sosial Instagram dan Tik-Tok tidak berpengaruh signifikan terhadap Purchase Intention konsumen Concrete. Store Atmosphere dan Price berpengaruh positif dan signifikan terhadap Purchase Intention konsumen Concrete Batu. Terdapat pengaruh secara simultan (bersama-sama) E-Wom, Store Atmosphere, dan Price terhadap Purchase Intention konsumen Concrete Batu.